Analysis of Transient Dynamic Behaviour of Spherical Cavity in Viscoelastic Soil Medium. (29th January 2013) - Dwivedi, J. P.; Singh, V. P.; Lal, Radha Krishna
Abstract : Stress, displacement, and pore pressure of a partially sealed spherical cavity in viscoelastic soil condition have been obtained in Laplace transform domain. Solutions of axisymmetric surface load and fluid pressure are derived.